Coma - Crichton, Michael, 1942-2008; Bujold, Geneviève.; Douglas, Michael, 1944-; Ashley, Elizabeth, 1939-; Cook, Robin, 1940- (Burbank, CA : Warner Home Video, 2010)
A young woman doctor is determined to discover why healthy patients are slipping into irreversible comas during routine operations and uncovers a secret medical research facility.
Based on the novel by Robin Cook.
Genevieve Bujold, Michael Douglas, Elizabeth Ashley, Rip Torn, Richard Widmark.
MPAA rating: PG.
DVD.
In English or French with optional English or French subtitles.
Keywords: Medical drama; Coma -- Drama; Cook, Robin, -- 1940- -- Film adaptations; Detective and mystery films; Fiction films; Based on the book; Feature films; Horror films; Detective films; Mystery films